New dimensions in ecological economics : integrated approaches to people and nature - Dovers, Stephen; Stern, David I.; Young, Michael D. (Cheltenham, U.K. : Northampton, Mass., USA : Edward Elgar Pub., 2003)
Drawing on the biophysical sciences, public policy, geography, economics, exploratory research and the behavioural sciences, this book offers reviews and prescriptions for the future of ecological economics, placing particular emphasis on complex sustainability problems.
Includes bibliographical references and index.
lje 25/08/16
Loans
Keywords: Environmental economics; Ecology - economic aspects